K*0 production in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, and 39 GeV from the RHIC beam energy scan - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2023)
We report the measurement of K*0 meson at midrapidity (|y|< 1.0) in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, and 39 GeV collected by the STAR experiment during the Relativistic Heavy Ion Collider (RHIC) beam energy scan program. The transverse momentum spectra, yield, and average transverse momentum of K*0 are presented as functions of collision centrality and beam energy. The K*0/K yield ratios are presented for different collision centrality intervals and beam energies. The K*0/K ratio in heavy-ion collisions are observed to be smaller than that in small-system collisions (e+e and p+p). The K*0/K ratio follows a similar centrality dependence to that observed in previous RHIC and Large Hadron Collider measurements. The data favor the scenario of the dominance of hadronic rescattering over regeneration for K*0 production in the hadronic phase of the medium.